The Commons as a New Sector of Value-Creation - Bollier, David (Kosmos, 2008)
Let me start with a bit of wisdom I once picked up from Thomas Berry, a historian of cultures who has said, “The universe is the communion of subjects, not a collection of objects.” This epigraph encapsulates the monumental shift that I believe we are undergoing as we move into a new kind of cultural if not economic reality. This article was originally published in the Fall | Winter 2008 issue of Kosmos Journal. To download a PDF version of this article, please click here.
Keywords: commons

The revenge of ideas: Karl Polanyi and Susan Strange - Halliday, Fred (openDemocracy, 2008)
Keywords: STRANGE, Susan